As‐Cast Ternary Organic Solar Cells Based on an Asymmetric Side‐Chains Featured Acceptor with Reduced Voltage Loss and 14.0% Efficiency. (22nd January 2020) - Chen, Xuebin; Kan, Bin; Kan, Yuanyuan; Zhang, Ming; Jo, Sae Byeok; Gao, Ke; Lin, Francis; Liu, Feng; Peng, Xiaobin; Cao, Yong; Jen, Alex K.‐Y.
Abstract: A new small‐molecule nonfullerene acceptor based on the benzo[1, 2‐ b :4, 5‐ b ′]dithiophene (BDT) fused central core with asymmetrical alkoxy and thienyl side chains, namely TOBDT, is designed and synthesized. The alkoxy unit helps narrow the bandgap, and thienyl side chain helps enhance the intermolecular interaction. As a result, TOBDT is suitable to match the deep‐lying highest occupied molecular orbital (HOMO) of polymer donor PM6 . Then, a strong crystalline acceptor IDIC is introduced as the third component to fabricate as‐cast nonfullerene ternary devices to achieve absorption and morphology control. Addition of IDIC not only mixes well with TOBDT but modulates the morphology of the blend film, which helps to balance the charge transport properties and reduce the photovoltage loss of ternary devices. All these contribute to synergetic improvement of J sc, V oc, and fill factor parameters, leading to a power conversion efficiency of 14.0% for the as‐cast fullerene‐free ternary device. Abstract : A new nonfullerene acceptor (TOBDT) with asymmetrical side chains is rationally designed and reported. Compared to the PM6:TOBDT binary devices, the as‐cast ternary devices based on PM6:IDIC:TOBDT obtain improved J sc, V oc, and fill factor values simultaneously, leading to a high power conversion efficiency of 14.0%, which is among the best reported for as‐cast fullerene‐free ternary devices.